Structure-MR damper reliability analysis using weighted uniform simulation method. (August 2020) - Bagherkhani, Ali; Baghlani, Abdolhossein
Abstract: In this study, the reliability assessment of the system of structure-MR damper in controlling seismic responses of the structure via semi-active control is studied. In this regard, numerical results are presented for two different examples including three and ten-storey shear structures. The limit state functions are defined based on the control responses obtained from the use of MR dampers in the structure stories. By defining several uncertainties in parameters of the structure-MR damper system, probability of failure of structure is obtained using weighted uniform simulation (WUS) method and compared with the results of traditional Monte Carlo Simulation (MCS). Moreover, the most probable point of failure, which cannot be calculated by MCS, is determined for each uncertain event. Graphs of system reliability are derived and interpreted. The results show satisfactory performance of the WUS method in the reliability analysis of smart structures. The results also indicate that reliability of the system is highly dependent on the mass uncertainty of the structure. Moreover, the highest probability of failure takes place when all parameters are considered to be simultaneously uncertain.